Local and global behavior of walls with cut-out openings in multi-story reinforced concrete buildings. (15th May 2019) - Sabau, Cristian; Popescu, Cosmin; Bagge, Niklas; Sas, Gabriel; Blanksvärd, Thomas; Täljsten, Björn
Highlights: Robustness of multi-story load-bearing wall structure via non-linear FEA. Response of axially loaded walls with cutout openings. Influence of cutout openings on structural robustness. Abstract: This paper presents the finite element analysis (FEA) results of a multi-story reinforced concrete (RC) building having precast and cast-in-place load bearing walls. Door-type cut-out openings (height: 2.1 m, width: 0.9–4.4 m) were created at the first and second story of the building. Results from experimental tests on axially loaded RC panels were used to verify the modeling approach. The influence of cut-out openings on the response of individual RC panels, failure modes, and load redistribution to adjacent members under increasing gravitational loads was analyzed. Moreover, the wall bearing capacities obtained from FEA were compared with the values calculated from design equations. The results revealed that the robustness of multi-story buildings having RC load bearing wall systems decrease considerably with the creation of cut-out openings. However, owing to the initial robustness of the buildings, large cut-out openings could be created under normal service conditions without strengthening of the building structure. Furthermore, design equations provided very conservative predictions of the ultimate axial capacity characterizing the solid walls and walls with small openings, whereas similar FEA and analytically predicted capacities were obtained for walls with large openings.